Rola współczesnych jarmarków miejskich w upowszechnianiu niematerialnego dziedzictwa kulturowego (na przykładzie Jarmarku Jagiellońskiego w Lublinie) - Kraczoń, Katarzyna (Studia Etnologiczne i Antropologiczne, 2014)
The article shown the role that contemporary urban markets have in the dissemination of cultural heritage. Author discusses the basic principles of the Convention of 2003, the scope of cultural heritage and the definition of „protection”. Next shows the ideas, goals and the most important events of Jagiellonian Fair, showing the positive aspects and risks associated with the promotion of cultural heritage. Initiatives and venture fairs shows the potential of cultural fairs not only the city but also the entire country and the eastern part of the European Union.